STUDI DESKRIPTIF VIDEO PEMBELAJARAN MATH MAGIC SeMUT UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN SISWA SEKOLAH DASAR: Media Pembelajaran Math Magic SeMUT untuk Peningkatan Kemampuan Berhitung (Adi Widya: Jurnal Pendidikan Dasar, 2024)
Learning Mathematics in Elementary School has not been able to improve students’ numeracy skills to the fullest, one of the reasons because many students think that mathematics is a difficult science and the explanations obtained related to the material cannot be understood by students properly. The use of monotonous teaching methods without any innovation makes students easily bored and less focused on understanding the materials during learning. This study aims to determine the increase in students’ numeracy skills after using learning media in the form of video Math Magic Trick SeMUT (Stiped Multiplication Trick). The research orientation that will be discussed is the operation of multiplying integers. The research was conducted in class IV SDNU Al Istiqomah Gresik with 9 students as subjects, 3 male students and 6 female students. This type of research uses descriptive quantitative research. Sampling techniques using observation with test instruments. The research method uses a pre-test and post-test. The final research show that there is an increase in students multiplication counting skills after applying video education the Math Magic SeMUT.